Revitalisasi Kesenian Tari Topeng sebagai Media Dakwah - Yayah Nurhidayah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2017)
Mask dance is one of the artistic potential of traditional media can be used as an alternate to the development of Islam. Elements of traditional and communicative nature of the performing arts, enabling to serve as an effective medium of information, without losing the element of entertainment. Unfortunately, the art of dance performances mask yet empowered as a package for maximum performance as well as guidance. the role of the mask dance used functioned as a medium for the spread of Islam, gradually shrinking. Globalization has led to the emergence of modern cultures and marginalized traditional art, art that potential existence is increasingly squeezed by the presence of popular art, and gradually abandoned his fans and Mask dance more exclusive. Therefore, needs to be revitalized, especially the function and role of the missionary expansion in the future.Tari topeng merupakan salah satu potensi kesenian tradisional yang dapat dijadikan sebagai media aternatif untuk pengembangan dakwah Islam. Unsur tradisional dan sifat komunikatif dari seni pertunjukkan tersebut, memudahkan untuk dijadikan sebagai media penerangan yang efektif, tanpa harus kehilangan unsur hiburannya. Sayangnya, seni pertunjukkan tari topeng belum diberdayakan secara maksimal sebagai paket tontonan sekaligus tuntunan. Peran tari topeng yang dulu difungsikan sebagai media syiar Islam, lambat laun menyusut. Arus globalisasi telah mendorong munculnya kebudayaan-kebudayaan modern dan memarginalisasi kesenian tradisonal, sehingga seni yang potensial ini keberadaannya makin terjepit oleh keberadaan seni populer, dan berangsur-angsur ditinggalkan penggemarnya sehingga tari topengpun makin ekslusif. Oleh karena itu, perlu direvitalisasi terutama makna, fungsi dan perannya untuk pengembangan dakwah di masa depan.